The ethics of capital punishment a philosophical investigation of evil and its consequences - Kramer, Matthew H., 1959- (Oxford : Oxford University Press, 2011)
Taking a fresh look at a central controversy in criminal law theory, 'The Ethics of Capital Punishment' presents a rationale for the death penalty grounded in a theory of the nature of evil and the nature of defilement.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 21, 2012).
Keywords: Capital punishment -- Moral and ethical aspects